Synthesis, Growth and Characterization of a Non-Linear Optical Crystal: Glycine Lead acetate (GLA). (2022) - Sankar, K.; Rajasekaran, R.; Umadevan, I.; Rangasamy, Baskaran; Ragupathi, C.; Vetrivelan, V.
Abstract: A new non-linear optical material, glycine lead acetate (GLA) was synthesized and crystal was grown by slow evaporation growth technique at constant temperature from its aqueous solution. The Lattice Parameters for the grown crystal were determined using single crystal XRD. The crystalline nature of new crystal was confirmed by powder XRD pattern. The Presence of various functional groups has been identified by using FTIR Spectral analysis ranging between 500 and 4000 cm −1 . The UV – Vis – NIR Spectroscopic study revealed that the grown crystal has good optical transmittance and the band gap energy was calculated to be 5.17ev. The thermal stability of the complex was studied by TG- DTA analysis and found that it is stable up to 214°C. The dielectric constant and dielectric loss has been studied as a function of frequency for various temperatures. The Second harmonic generation behaviour of GLA Crystal was tested by Kurtz –Perry powder technique and it is found to be 1.12 times than that of KDP Crystal.